2022
DOI: 10.1186/s12913-022-07968-6
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation during the COVID-19 pandemic in Sweden: a survey of use and perceptions among physiotherapists treating people with neurological diseases or older adults

Abstract: Background  Telerehabilitation, i.e. rehabilitation at a distance using Information and Communication Technology (ICT), is a promising avenue for improving health among people with neurological diseases or older adults who often experience limited access to services. Still, little is known about physiotherapists’ use, perceptions and needs with regards to telerehabilitation services. Aims To describe physiotherapists use and perceptions of, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
0
24
0
2
Order By: Relevance
“…mobile phones, patient monitoring devices and applications) [ 25 ]; a promising avenue for providing equal and accessible health promotion services to people post stroke or TIA. Despite patients and healthcare professionals reporting high levels of acceptance towards mHealth both globally [ 26 ] and locally [ 27 ], implementation of mHealth services has been limited during the Covid-19 pandemic in Sweden [ 27 ]. mHealth can be beneficially adopted at various points during the patient-clinician therapeutic process from assessment, through to intervention, support, and follow-up [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…mobile phones, patient monitoring devices and applications) [ 25 ]; a promising avenue for providing equal and accessible health promotion services to people post stroke or TIA. Despite patients and healthcare professionals reporting high levels of acceptance towards mHealth both globally [ 26 ] and locally [ 27 ], implementation of mHealth services has been limited during the Covid-19 pandemic in Sweden [ 27 ]. mHealth can be beneficially adopted at various points during the patient-clinician therapeutic process from assessment, through to intervention, support, and follow-up [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various devices using ICT are being developed, but they are not widely used because of the lack of governance, including related laws, policies and national programs; awareness of children and their families; and services. In addition, equipment for service is expensive, and it is difficult to access the service environment physically and socially (Raja, 2016; experienced a long period of pandemic, the demand for ICT-based services for the disabled has increased (Alsem et al, 2020;, and many organizations are preparing for ICT-based services (Bezuidenhout et al, 2022;Park et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, equipment for service is expensive, and it is difficult to access the service environment physically and socially (Raja, 2016; Ryan & Quinlan, 2018; WHO, 2015). However, as we have recently experienced a long period of pandemic, the demand for ICT‐based services for the disabled has increased (Alsem et al, 2020; Chadwick et al, 2022), and many organizations are preparing for ICT‐based services (Bezuidenhout et al, 2022; Park et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 31 A study of Swedish physiotherapists reported that most did not take up remote consultations readily, but felt there were potential significant benefits, for example,, use of the chat function, SMS messages, online surveys and sending treatment plans via the internet. 32 …”
Section: Discussionmentioning
confidence: 99%
“…31 A study of Swedish physiotherapists reported that most did not take up remote consultations readily, but felt there were potential significant benefits, for example,, use of the chat function, SMS messages, online surveys and sending treatment plans via the internet. 32 The use of EBD methods highlighted some important elements to delivering group-based pain education and rehabilitation. The importance of 'hope' as a concept in relation to PAINEDU was raised and maintained throughout the session.…”
Section: Discussionmentioning
confidence: 99%